Residual and ovicidal efficacy of essential oil‐based formulations in vitro against the donkey chewing louse Bovicola ocellatus. Issue 1 (2nd November 2015) - SANDS, B.; ELLSE, L.; WALL, R.
Abstract: Essential oils have shown good experimental potential as novel veterinary ectoparasiticides. However, if they are to be used as veterinary products, they must be available in formulations that are suitable for practical application against specific ectoparasites. Here, the efficacies of formulations containing 5% (v/v) lavender or tea tree oil, in combination with two emulsifiers [a surfactant, 5% (w/v) N ‐lauroylsarcosine sodium salt (SLS), and a soluble polymer, 5% (w/v) polyvinylpyrrolidone (PVP)], with or without 10% coconut oil, were tested in contact bioassays against the donkey chewing louse Bovicola ocellatus (Piaget) (Phthiraptera: Trichodectidae). Residual activity was quantified in open and closed containers; ovicidal efficacy was also examined. Exposure to either of 5% (v/v) lavender or tea tree oils with SLS or PVP resulted in louse mortality of 100%, but when coconut oil was included as an excipient, significantly lower efficacy was recorded. However, the formulations became significantly less effective after 2 h in open containers and 40 h in closed containers. The results confirm that the residual activity of essential oils is relatively transitory and the addition of 10% coconut oil does not prolong the period of insecticidal activity by slowing essential oil evaporation. Too short a period of residual activity is likely to be a significant impediment to the effective practical use of essential oils. However, unlike many synthetic pediculicides, the essential oils tested here were highly ovicidal, which suggests that prolonged residual activity may not be essential to kill newly hatched nymphs after treatment.